福衛三號與EISCAT特羅姆瑟雷達站在極光區全電子含量觀測之比較 - 饒詒智; Jao, Yi-Chih (2016)
福爾摩沙衛星三號利用GPS掩星方式反演電子密度，並使用了球對稱的方式，假設一個近地球軌道衛星，經過地球兩端，電子密度為球對稱，兩端的中心點為切點，以此方式決定出經緯度、高度與電子密度。但是實際上地球並非是完美的球狀，且近地球軌道衛星所經過的電子密度，也並非球對稱和左右相等。 本研究利用EISCAT雷達觀測站的數據來比較福爾摩沙衛星三號的數據，使用電子密度與高度的關係計算出垂直總電子密度含量，並且比較在不同參數與電離層的活動下，EISCAT雷達觀測站與福爾摩沙衛星三號的垂直總電子密度含量誤差百分比。 本篇論文中將討論太陽輻射通量指數、地磁擾動強度、地球磁暴指數、向東極光電噴流強度、向西極光電噴流強度、極光電噴流參數、角度這些參數對於垂直總電子密度含量的誤差分析，分析中發現此雷達地點晚上平均誤差高於白天，且雷達觀測站地點落在極光區範圍，所有資料中呈現晚上較容易有電噴流經過，此地點造成誤差的最主要原因為電噴流影響了電子的飄移，造成電子密度的改變，使得有電噴流經過的資料誤差較大，去除最大的誤差影響，造成第二大因素為福衛三號與雷達站至地心的夾角，夾角越大誤差越大，也就是福衛三號離觀測地點越遠誤差相對越大。 FORMOSAT-3/COSMIC satellites use radio occultation and Abel inversion to observe the vertical electron density profile. The method assumes the density of the Earth is spherically symmetric. But the assumption may not correspond to real ionospheric situations. Therefore, this method of observations may lead to inaccurate results. This study aims to find out the factor that is important in affecting the discrepancy between the observed TEC by FORMOSAT-3/COSMIC and the radar observatory. We apply the observed electron density profiles to calculate TEC. Parameters such as F10.7, Dst index, Kp index, AE index, AU index, AL index, local time and angle between the satellite and radar observations are examined as possible factors for the discrepancy. Finally, this study finds the discrepancy in TEC between FORMOSAT-3/COSMIC and radar observations is mainly due to westward electrojet and eastward electrojet. The secondary reason is the angle between the observation locations of FORMOSAT-3/COSMIC and the radar observatory subtended at the center of the Earth. We find that the larger this angle, the larger the percentage error for the FORMOSAT-3/COSMIC observations.